2017
DOI: 10.1080/02699052.2017.1339124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychiatric symptomatology on neuropsychological assessment performance in persons with TBI: A comparison of OEF/OIF veteran and civilian samples

Abstract: Results showed worse neurocognitive performance (i.e. RBANS Total Index score) in the veteran sample relative to the civilian sample [F(1,99) = 3.92, p = .05, ƞ2 = .04], particularly on tasks measuring attentional capabilities [F(1,99) = 9.18, p = .003, ƞ2 = .09]. Additional analyses found that after controlling for post-traumatic stress disorder symptomatology, differences were no longer significant. Broad correlations between measures also showcased attenuated relationships after controlling for both post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…452 Moreover, interactions might exist between cognitive performance and the presence of psychological disorders such as post-traumatic stress disorder or depressive symptoms, which might affect the reliability of neuropsychological assessment results. 453 The use of different approaches and combinations of instruments would depend on the level of disabilityeg, patients who have persistent postconcussion symptoms after mild TBI would have assessment needs different from those with disorders of consciousness after severe TBI. This need to accommodate different outcomes or levels of severity of impairment is concordant with the concept of the sliding dichotomy for outcome analysis of GOS or GOSE scores, in which the point of dichotomy of this measure is differentiated by initial baseline risk.…”
Section: Figure 12: Classification Of Outcome Of Traumatic Brain Injumentioning
confidence: 99%
“…452 Moreover, interactions might exist between cognitive performance and the presence of psychological disorders such as post-traumatic stress disorder or depressive symptoms, which might affect the reliability of neuropsychological assessment results. 453 The use of different approaches and combinations of instruments would depend on the level of disabilityeg, patients who have persistent postconcussion symptoms after mild TBI would have assessment needs different from those with disorders of consciousness after severe TBI. This need to accommodate different outcomes or levels of severity of impairment is concordant with the concept of the sliding dichotomy for outcome analysis of GOS or GOSE scores, in which the point of dichotomy of this measure is differentiated by initial baseline risk.…”
Section: Figure 12: Classification Of Outcome Of Traumatic Brain Injumentioning
confidence: 99%
“…It measures multiple aspects of cognitive functioning, and consists of five testing composites, that is, verbal memory, visual memory, processing speed, reaction time and impulse control 19The screening module of neuropsychological assessment battery (Digit Span) 18Wechsler Adult Intelligence Scale Version 4 (Digit Symbol Coding and Symbol Search) 20…”
Section: Methods and Analysismentioning
confidence: 99%
“…At present, the mainstream assessment of mTBI both in sports and in the primary/secondary healthcare setting involves the functional and symptomatic assessment of an individual using neurocognitive tests 15. These tests have significant limitations, particularly the lack of baseline/premorbid measurement in terms of sensitivity and specificity16 17 and the susceptibility to multiple confounding factors18 such as musculoskeletal injury and/or premorbid disability. This together with their requirement for a high level of engagement and concentration limits their application in outpatient clinic or pitch-side.…”
Section: Introductionmentioning
confidence: 99%
“…A sample of the studies reviewed found: mTBI was not responsible for poor performance on measures of attention, information processing, working memory, and mental calculation; i nstead, cognitive deficits were significantly related to current PTSD symptom-severity; 99,100 no significant difference was observed between veterans in a mTBI-only condition and the control group; 100 after controlling for their PTSD symptomatology, group differences disappeared between veterans with past TBI and control participants, 101,102 and that factors such as number of lifetime concussions, and if the veteran experienced AOC versus LOC did not affect cognitive test performance. 103 The conclusions offered by a number of the authors could be quite strong and included: That neurocognitive differences in OEF/OIF veterans might be better explained by PTSD than blast exposure history; in agreement with other investigations remote combat-related mTBI does not in and of itself contribute to objective cognitive impairment, 104 and findings fall within those of numerous meta-analyses conducted on general TBI data sets that acute neurocognitive effects resolve within several weeks to months and that there is no dose-response relationship between the effects of a single and multiple concussions on neuropsychological functioning.…”
Section: Neuropsychological Functioningmentioning
confidence: 99%